CRITICAL REVIEW OF DRUG INDUCED CARDIOTOXICITY W.S.R. TO GARA VISHA - Matre Akash T,; Anjankar Meghsham P,; Nikam Ashwin V,; Pawade Uday V, (International Journal of Ayurveda and Pharma Research, 2020)
Cardiotoxicity is a condition when there is damage to heart muscles by a toxin. It has many causes but drug induced cardiotoxicity is more common. Agadtantra is one of the eight clinical branches of Ayurveda. It deals with Visha, their characteristics, manifestations and treatment. Cardiovascular diseases and cancer are the most common causes of death in India. Out of which, heart failure is a major cause. Cardiotoxicity is one reason for heart failure; it may cause due to some common drug categories like anticancer agents, monoclonals, antihypertensives, antidepressants etc. No specific antidote treatment for drug induced cardiotoxicity is available till now. Currently it is managed by using general line of treatment and symptomatic treatment. Gara visha (Artificial Poison) is the type of Samyogaja visha (Unnatural poison or chemically prepared poison) which is prepared by the combination of either poisonous or non-poisonous substances. Thorough literature review has been conducted on modern aspect of drug induced cardiotoxicity and classical aspect of Gara visha. It is found that there is positive correlation between drugs induced cardiotoxicity and Gara visha. Hence, it is concluded that various treatment modalities useful in Gara visha can be effective in drug induced cardiotoxicity. Present article will be helpful for researchers to explore different dimensions of treatment of drug induced cardiotoxicity.